2004
DOI: 10.1007/s10728-004-6636-9
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and Competence in Child and Adolescent Psychiatry

Abstract: Capacity and competence in the field of child and adolescent psychiatry are complex issues, because of the many different influences that are involved in how children and adolescents make treatment decisions within the setting of mental health. This article will examine some of the influences which must be considered, namely: developmental aspects, the paradoxical relationship between the need for autonomy and participation and the capacity of children, family psychiatry, and the duty of care towards children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Therefore, despite how clients arrive to counseling, positive treatment outcomes remain achievable. Although minimal research exists examining the experiences of adolescents who enter treatment involuntarily, researchers suggested that counselors' early engagement of adolescent clients in the treatment process significantly increased clients' motivation and perceived treatment effectiveness (Tan & Fegert, 2004).…”
Section: Adolescent Help Seekingmentioning
confidence: 99%
“…Therefore, despite how clients arrive to counseling, positive treatment outcomes remain achievable. Although minimal research exists examining the experiences of adolescents who enter treatment involuntarily, researchers suggested that counselors' early engagement of adolescent clients in the treatment process significantly increased clients' motivation and perceived treatment effectiveness (Tan & Fegert, 2004).…”
Section: Adolescent Help Seekingmentioning
confidence: 99%
“…(4) perceived stigma related to medication; (5) viewing medication as unnecessary; (6) perceived unhelpfulness of medication; (7) mistrust of medication or prescribers; (8) concerns about long-term effects of medications, and (9) preferring self as is/without medication.…”
Section: Samplementioning
confidence: 99%
“…As minors and dependents, youth are asked to give assent, but are not given the right of consent, which is a right to either accept or deny treatment; this is reserved for their parents or legal guardians [6][7][8][9]. Because many youth receiving psychiatric treatment are not full participants in decision-making [10], a question arises about the extent to which youth prescribed psychotropic medication are committed to this treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Research also suggests that children with attention-deficit/hyperactivity dis- Even if they have competence to make decisions, because of their close relationships with their parents, many children and adolescents may prefer to have a group or joint decision-making model, making decisions together with parents and other trusted adults. Children and adolescents who are suffering from mental disorders are probably more likely to prefer, and benefit from, a joint decision-making model [35].…”
Section: : "States Parties Undertake To Ensure the Child Such Protectmentioning
confidence: 99%